2014
DOI: 10.1086/674443
|View full text |Cite
|
Sign up to set email alerts
|

Variation between Self- and Mutual Assessment in Animal Contests

Abstract: Limited resources lead animals into conflicts of interest, which are resolved when an individual withdraws from a direct contest. Current theory suggests that the decision to withdraw can be based on a threshold derived from an individual's own state (selfassessment) or on a comparison between their own state and their opponent's (mutual assessment). The observed variation between these assessment strategies in nature does not conform to theory. Thus, we require theoretical developments that explain the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 64 publications
(122 reference statements)
2
44
0
Order By: Relevance
“…Briffa & Elwood, 2005;Glass & Huntingford, 1988;Kelly & Godin, 2001). Selection should therefore favour individuals that make appropriate decisions based on assessment of the costs and benefits of fighting (Maynard Smith & Parker, 1976;Parker, 1974;Parker & Rubenstein, 1981), although such assessment does not always occur (Elwood & Arnott, 2012;Mesterton-Gibbons & Heap, 2014). There are two classes of theoretical models of animal contests that differ in their assumptions about the information-gathering abilities of contestants (reviewed by Arnott & Elwood, 2009a;Elwood & Arnott, 2012).…”
mentioning
confidence: 99%
“…Briffa & Elwood, 2005;Glass & Huntingford, 1988;Kelly & Godin, 2001). Selection should therefore favour individuals that make appropriate decisions based on assessment of the costs and benefits of fighting (Maynard Smith & Parker, 1976;Parker, 1974;Parker & Rubenstein, 1981), although such assessment does not always occur (Elwood & Arnott, 2012;Mesterton-Gibbons & Heap, 2014). There are two classes of theoretical models of animal contests that differ in their assumptions about the information-gathering abilities of contestants (reviewed by Arnott & Elwood, 2009a;Elwood & Arnott, 2012).…”
mentioning
confidence: 99%
“…Recently, Mesterton‐Gibbons et al. () explored the role of mistakes in property games by introducing ownership uncertainty into both a one‐shot and an iterated Hawk–Dove game. They showed that if intruders sometimes believe themselves to be owners, then the resulting confusion over ownership can not only increase the frequency of fighting in the one‐shot game – consistent with the higher‐intensity fights between individuals observed in P. aegeria ‘when both males "believe" themselves to be owners of the sunspot in which the interaction occurs’ (Wickman & Wiklund, , p. 1208) – but also broaden the range of conditions under which Bourgeois behaviour is evolutionarily stable.…”
Section: Model Extensionsmentioning
confidence: 79%
“…animal contests, and there is a considerable number of cases where animals seem to use a mixed assessment strategy (Mesterton-Gibbons & Heap 2014;Palaoro et al 2014;Guillermo-Ferreira et al 2015). The aforementioned evidence of chemical communication was gathered from open-water freely living species rather than burrowing crayfish.…”
Section: Discussionmentioning
confidence: 99%